Intestinal barrier damage contributes to a higher prevalence of frailty in aging people living with HIV: a retrospective case control study in a Chinese cohort - Xu, Xiaolei; Ouyang, Jing; Yan, Jiangyu; Lu, Yanqiu; Harypursat, Vijay; Wu, Hao; Chen, Yaokai (Frontiers in Immunology, 2024)
Background It has been previously demonstrated that intestinal barrier damage is one of the underlying mechanisms leading to frailty in non-HIV-infected aging populations. However, there is a paucity of direct evidence which demonstrates the association between intestinal barrier damage and frailty in people living with HIV (PLWH). Methods The present study is a retrospective case control study. Participants older than 50 years old were stratified into a frail/pre-frail group (case group) and non-frail group (control group) according to the Fried frailty phenotype. We collected and curated data concerning socio-demographic variables, psychological states and social functioning, and clinical information associated with the identification of biomarkers of intestinal barrier damage, microbial translocation, and levels of inflammatory cytokines of participants. Results The case group had significantly higher levels of Reg-3α (p=0.042) and I-FABP (p=0.045) compared to the control group. We further observed, after adjusting for confounding factors by logistic regression analysis, that I-FABP levels remained significantly higher in the case group compared to the control group (p=0.033). Also, Fried Phenotype scores positively correlated with I-FABP levels (rs=0.21, p=0.01), LPS levels (rs=0.20, p=0.02), and sCD14 levels (rs=0.18, p=0.04). Moreover, the study confirmed both the positive correlation between inflammatory cytokines (IL-6 and IP-10) with frailty in aging PLWH, and between inflammatory cytokines (IL-6, IL-8 and IP-10) with biomarkers of intestinal barrier dysfunction in older PLWH. Conclusion The present study indicates that the inflammation induced by intestinal barrier damage/dysfunction is likely to contribute to frailty in aging PLWH.